Low‐Cost Silicon Nitride from β‐Silicon Nitride Powder and by Low‐Temperature Sintering. Issue 2 (8th August 2013) - Kondo, Naoki; Hotta, Mikinori; Ohji, Tatsuki
Abstract : Aiming to manufacture low‐cost silicon nitride components, a low‐cost β powder was chosen as a raw powder and low‐temperature sintering at 1550–1600°C under atmospheric pressure nitrogen was carried out. The silicon nitride from β powder with 5 wt% Y2 O3 and 5 wt% MgAl2 O4 additives and sintered at 1600°C for 8 h was successfully densified, and it exhibited moderate strength and toughness of 553 MPa ± 22 and 3.5 MPa m 1/2, respectively. The results indicate that the low‐temperature sintering of the low‐cost β powder has a potential to reduce cost of components.